An Exponential Melanoma Trend Model - Hallberg, Örjan (International Journal of Statistics in Medical Research, 2015)
The present study investigated whether whole population exposure to radiation introduced by radio broadcasting and cell phone systems might explain recent increases in melanoma trends in Nordic countries or not. Trends were modeled using a single exponential function of the time each age group has been living in the new environment since an environmental change took place. The results clearly show that melanoma incidences started to increase exponentially by the time lived as an adult since 1955 and that a second trend break occurred in 1997. We searched best fit between calculated and reported age-standardized rates by parameter variation, and compared calculated with reported age-specific rates without further parameter adjustments. Local variations of breast cancer, lung cancer and all cancers together significantly correlated with corresponding local melanoma rates in Sweden. Increasing cancer trends since around 1997 seem related to a population covering environmental change effective from early 90’s. We conclude that this exponential trend model can be a useful tool in understanding responses to sudden environmental changes.